Prevalence of Opisthorchis viverrini infection among villagers harboring Opisthorchis-like eggs - Sukontason K.L. (2014)
The precise occurrence of Opisthorchis viverrini infection in humans, who were positive for Opisthorchis-like eggs in a stool examination, was determined using the potassium permanganate staining method. In the 68 specimens examined, there were more individual O. viverrini eggs (38.24%) than singular Haplorchis taichui eggs (29.41%). One-fourth of the total specimens contained a mixed infection of O. viverrini and H. taichui eggs. The median ratio of O. viverrini: H. taichui eggs in mixed infection cases was 2.29 (min = 1, max = 17.5). It is suggested that chemotherapy with praziquentel treatment should be given to patients who are positive for O. viverrini-like eggs.